2016
DOI: 10.1111/pace.12787
|View full text |Cite|
|
Sign up to set email alerts
|

One‐Year Clinical Outcome of Pulmonary Vein Isolation Using the Second‐Generation Cryoballoon: A Meta‐Analysis

Abstract: CB-2G is highly effective in the treatment of both paroxysmal AF and persistent AF. The "no-bonus" strategy is as effective as the "bonus" strategy in terms of 1-year clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Although increased operator experience may also have contributed to improved results, advances in both CB technology (second‐generation CB, 78.1% freedom from AT) and RF ablations (CF‐sensing RF, 78.2% freedom from AT) have certainly been associated with increased procedural success rates. In a meta‐analysis of 15 studies involving 2,363 patients who underwent CB2 ablations, freedom from AT after 1‐year follow‐up was approximately 82% and 70% for paroxysmal and persistent AF, respectively . The mechanisms for improved efficacy with CB2 are likely directly related to structural changes in the device, which have optimized the refrigerant flow, producing a more uniform freezing zone that spans the entire distal half of the balloon surface …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although increased operator experience may also have contributed to improved results, advances in both CB technology (second‐generation CB, 78.1% freedom from AT) and RF ablations (CF‐sensing RF, 78.2% freedom from AT) have certainly been associated with increased procedural success rates. In a meta‐analysis of 15 studies involving 2,363 patients who underwent CB2 ablations, freedom from AT after 1‐year follow‐up was approximately 82% and 70% for paroxysmal and persistent AF, respectively . The mechanisms for improved efficacy with CB2 are likely directly related to structural changes in the device, which have optimized the refrigerant flow, producing a more uniform freezing zone that spans the entire distal half of the balloon surface …”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 15 studies involving 2,363 patients who underwent CB2 ablations, freedom from AT after 1-year follow-up was approximately 82% and 70% for paroxysmal and persistent AF, respectively. 27 The mechanisms for improved efficacy with CB2 are likely directly related to structural changes in the device, which have optimized the refrigerant flow, producing a more uniform freezing zone that spans the entire distal half of the balloon surface. 6 Part of the technical challenges of RF PVI includes maintaining ideal electrode tissue contact force.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45] A meta-analysis of 15 studies on the second-generation, cryoballoon found a 1-year success rate of 82% in patients with paroxysmal AF and 70% in patients with persistent AF. 46 A meta-analysis of 10 studies comparing the first-and second-generation devices found improved efficacy (odds ratio, 0.34; P<0.00001), shorter procedure time (mean difference=−0.8, P<0.00001), and shorter fluoroscopy time (mean difference=−1.0, P<0.00001) with the second-generation device. 40 Although longer-term data with the second-generation cryoballoon are limited, 1 study found a 2-year success rate of 73% after a single procedure and 88% with multiple procedures.…”
Section: Cryothermal Ablationmentioning
confidence: 99%
“…In almost all patients who underwent the redo procedure, at least one reconnected PV was documented, and the electrical reconnections were ablated using either CB-2 or RF ablation. In previous studies, the PV electrical reconnection primarily reflected incomplete CB contact and anatomical variations, causing misalignment with the CB and PVs that resulted in a longer time to PVI or a warmer 1-min or end-procedure nadir temperature [27]. However, the number of PV electrical reconnections was not sufficient to evaluate the predictors of PV electrical recurrence in these patients.…”
Section: Discussionmentioning
confidence: 92%
“…Using CB-2, Metzner et al reported an incidence of 81 % freedom from atrial tachyarrhythmia in patients with PAF during a mean followup time of 440 ± 39 days [8]. In addition, a recent meta-analysis revealed an 82 % 1-year clinical success rate in PAF patients using the "no bonus" protocol and an 83 % success rate with the "bonus" strategy using CB-2 [27]. Although the 1-year outcomes of nonbonus studies were promising compared with the bonus studies, data for long-term follow-up with bonus freeze protocols are limited.…”
Section: Discussionmentioning
confidence: 99%